Facial growth dynamics dictate optimal facemask fitting during the first year of life - Haase, Bianca; Badinska, Ana-Maria; Sowula, Julian; Springer, Laila; Schwarz, Christoph; Stauch, Anette; Weismann, Christina; Poets, Christian F.; Wiechers, Cornelia (Acta paediatrica, 2024)
Aim The aim of this study is to prevent mask leak during ventilation in infant emergencies, appropriate facemask fitting is essential. Therefore, we investigated facial profiles during the first year of life and their correlation with the correct sizing of masks. Methods This is a post hoc subgroup analysis of 32 healthy term infants, based on a prospective observational study performed from September 2018 to December 2019 in Tuebingen, Germany. In 3-monthly intervals, facial aspects were measured based on anatomical landmarks in three-dimensional frontal photographs to describe their changes across the first year of life. All infants were awake and breathing spontaneously; none required any anaesthesia. Results In 130 3D images, mean distance between nasion and gnathion was 54 mm (3.3) measured at birth and 70 mm (3.5) at age 12 months. Gompertz models showed relevant growth-related changes in the facial profile in vertical but not horizontal direction. Vertical growth occurred mainly in the first 6 months. Boys and girls differed by an average of about 2 mm (boys >girls). Conclusion Based on our findings, it should now be verified whether the 50 mm facemasks are suitable for infants from birth to 2 months of age, respectively, the 60 mm version for infants aged three to 12 months.